A review of grout materials in geothermal energy applications. (May 2021) - Mahmoud, Montaser; Ramadan, Mohamad; Pullen, Keith; Abdelkareem, Mohammad Ali; Wilberforce, Tabbi; Olabi, Abdul-Ghani; Naher, Sumsun
Abstract: Ground heat exchangers are surrounded by grout material, making it one of the most important components in geothermal energy applications since it significantly affects the system's thermal performance. The current study reviews the different types of grout materials and compares their thermophysical properties. The most critical parameter is the grout's thermal conductivity in which it always presents a proportional relation with the system's efficiency. Numerous factors are involved in this review to ascertain theier impact on the grouts' performance such as flowability, shrinkage, moisture content, freezing, heat capacity, strength, permeability, solubility and thermal imbalance. The different grouts compared are bentonite, cement, sand, graphite, controlled low-strength material, dolomite, and phase change materials. The literature shows that phase change materials are the best choices of grouting since they can provide high storage capacity, stability and temperature uniformity. The major problem of such materials is their low thermal conductivity. Thus, it is recommended to use composite phase change materials to enhance their thermal conductivity and increase the storage/retrieval rate.